Interferência longitudinal de pequenas estruturas na conectividade sedimentológica fluvial: bacia hidrográfica do baixo curso do Rio Piancó – semiárido paraibano - Castelo Branco, André Oliveira Trigueiro (2020)
In the Brazilian semiarid region, the human presence finds in the supply of water resources its greatest factor for the development of its activities. Coexistence with the semiarid region requires countless forms of adaptation and management by communities, municipalities, and other public spheres. In this region, the predominance of river behavior is intermittent and ephemeral regimes, with few exceptions. This characteristic requires a traffic infrastructure that allows the small rivers and streams bodies to be crossed even during the rainy season and that finds in wet passages a low-cost alternative, capable of supporting multiple levels of water flow. This work sought to evaluate the longitudinal influences provided by these structures to the river system and sedimentological connectivity. The spatial cutout was the low course hydrographic basin of the Piancó River, located in the municipalities of Coremas, Pombal, Cajazeirinhas, São Bentinho, and São José da Lagoa Tapada, in the State of Paraíba. For this purpose, dams, wet passages, and bridges along the hydrographic basin were raised and identified. Four wet passages were selected for analysis and diagnosis, and the effective capture areas of each structure were delimited, as well as the effective time scale. Using rain data from three rainfall stations, it was located in its historical series precipitation events capable of generating expressive sedimentological and morphological modifications, classifying it, therefore, into three types according to their magnitudes. In each wet passage analyzed sediment samples were collected and lateral profiles were drawn upstream and downstream of the structures to analyze the sediment’s destruction and deposition and the channel morphology. This provided the finding that the wet passages have the ability to act as elements of sediment interruption, especially the coarser ones, upstream and encourage the carving of the downstream channel. However, in exceptional flows, they allow the transmission of sediments, due to the level of clogging of the upstream channel riverbed. Thus, there is a common behavior of the river system and the wet passages over time, and a model of behavior divided into four stages was developed, considering not only the temporality but also the coexistence with precipitation events and their magnitudes. Comparing the stage model and the wet passages with other types of small longitudinal fluvial interventions present in the international literature, aesthetic and structural similarities were verified with the floodways and fords, but functionally the wet passages find strong similarities with check dams, weirs, and sand dams, for having a predisposition to retain sediments and alter the morphology of the channels where they are installed.